(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Research and innovation are fundamental components of university missions, contributing to academic excellence, economic growth, and societal progress. Universities act as key players in knowledge creation, policy development, and technological advancements. However, challenges such as limited funding, weak university-industry collaboration, and bureaucratic barriers hinder research efficiency. This paper explores the role of research and innovation in universities, their impact on global development, and strategies to enhance research ecosystems. Findings suggest that interdisciplinary research, increased funding, digitalization, and industry collaboration are essential for fostering an innovative academic environment.